Sistem Pesanan Makanan Menggunakan Kod QR - Zabidi, Nur Amirah; Hamzah, Mohd Hamdi Irwan (Applied Information Technology And Computer Science, 2021)
Food Ordering System using Code QR is an online application for Bistari Cafe. The current system for this bisnes is manually and the service for customers who dine in  is self-service. The purpose of this application is developed in accordance with the theme of self-service cafes for customers. With the application developed the customer only needs to place an order online without having to order manually to the payment counter. In addition, cafe employees can also waste paper to record orders and some features are developed for the convenience of both users. The Java programming language is the language used in this application and Firebase as the database server data.